Clinical factors predict surgical outcomes in pediatric MRI-negative drug-resistant epilepsy. (October 2016) - Arya, Ravindra; Leach, James L.; Horn, Paul S.; Greiner, Hansel M.; Gelfand, Michael; Byars, Anna W.; Arthur, Todd M.; Tenney, Jeffrey R.; Jain, Sejal V.; Rozhkov, Leonid; Fujiwara, Hisako; Rose, Douglas F.; et al.
Highlights: ⿢ 12/47 children with MRI-negative epilepsy were seizure-free 2.8 years after surgery. ⿢ 50% of children with single semiology and concordant ictal EEG were seizure free. ⿢ Clinical factors determine seizure outcomes in children with MRI-negative epilepsy. ⿢ Predictors: low seizure frequency, later age of onset, fewer pre-surgical AEDs. ⿢ ILAE type I-B cortical dysplasia was found in 17/47 patients. Abstract: Purpose: Lack of a potentially epileptogenic lesion on brain magnetic resonance imaging (MRI) is a poor prognostic marker for epilepsy surgery. We present a single-center series of childhood-onset MRI-negative drug-resistant epilepsy (DRE) and analyze surgical outcomes and predictors. Methods: Children with MRI-negative DRE who had resective surgery from January 2007 to December 2013 were identified using an institutional database. Relevant clinical, neurophysiological, imaging, and surgical data was extracted. The primary outcome measure was seizure freedom. Predictors of seizure freedom were obtained using multivariate logistic regression. Results: Out of 47 children with MRI-negative DRE, 12 (25.5%) were seizure free (International League Against Epilepsy [ILAE] outcome class I), after mean follow-up of 2.75 (±1.72) years. Seizure-free proportion was significantly higher in patients with single seizure semiology and concordant ictal EEG (50.0% vs. 15.2%, p  = 0.025). Multivariate analysis using only non-invasive pre-surgical data showed that children with daily seizures (OR 0.02, 95% CI < 0.001⿿0.55), and earlier onset of seizures (OR 0.72, 95% CI 0.52⿿0.99) were less likely to be seizure-free. Also, each additional anti-epileptic drug (AED) tried before surgery decreased the probability of seizure-free outcome (OR 0.16, 95% CI 0.04⿿0.63). Repeat multivariate analysis after including surgical variables found no additional significant predictors of seizure-freedom. Cortical dysplasia (ILAE type IB) was the commonest histopathology. Conclusion: Surgical outcomes in children with MRI-negative DRE are determined by clinical factors including seizure frequency, age of onset of seizures, and number of failed AEDs.